تعزیراتِ پاکستان میں تحفظ جان سے متعلق دفعات: اسلامی تعلیمات کی روشنی میں ایک مطالعہ: Provisions Regarding Sanctity of Life in Pakistan Penal Code: A Study in the Light of Islamic Teachings (Al-Qamar, 2018)
A person’s right to life, personal security, privacy, and ownership are the most basic of all the fundamental rights and liberties and are of concern to all legal systems and traditions. The right to life is the basic right from which all the others derive. The discussion of this fundamental right includes: the sanctity of life from the Islamic perspective, murder, unintentional killing, the death penalty and compensations for victims. The protection and sanctity of life is a non-negotiable principle because it is the pillar of civilization. Pakistan has legislation in this regard. The right to life is enshrined in Article 9 of the Constitution of the Islamic Republic of Pakistan. The Pakistan Penal Code stipulates punishment for murder under Qiṣaṣ and Diyah. The Pakistan Penal Code provides for the punishment of a murderer under four types of murder. However, there is no mention of Qasamah.
Keywords: Pakistan Penal Code; Human life; Islamic Sharīʻah